Corporate Environmental Responsibility of the Tourism Sector in Jordan - Hindiyeh, Khulood (2008)
Traditionally, environmental protection has been considered to be "in the public interest" and external to private life. Governments have assumed principal responsibility for assuring environmental management, and have focused on creating and preserving a safe environment. They have directed the private sector to adopt environmentally sound behaviour through regulations, sanctions and occasional incentives. Consequently Corporate Environmental Responsibility (CER) has been considered as part of the broader case of Corporate Social Responsibility (CSR).